THE EFFECTIVENESS OF BLENDED LEARNING DURING THE COVID-19 PANDEMIC A Case Study of the Department of English at AmmarThelidji University - Attia, Salah; Choucha, Brahim; Nouioua, Amina (Faculty of Letters and Foreign Languages Department of English, 2023)
The COVID-19 pandemic has brought about major changes to the educational system globally, including the widespread adoption of blended learning. Blended learning combines traditional face-to-face instruction with online learning and provides flexibility and convenience in delivering education. In this context, it is essential to evaluate the effectiveness of blended learning in the department of English at the University of Laghouatduring the pandemic. The present study aims at investigate the impact of blended learning on student learning outcomesin the department during the pandemic.Composed of three chapters, this paper, on one side, provided a theoretical background on blended learning and the main components needed for its viability as an approach to learning, while emphasizing its effectiveness and impact on students’ performance during the COVID-19 pandemic era in Algeria. On the other hand, the third chapter dealt with the practical part of this study, where EFL students were handed a questionnaire which was analyzed in the data analysis section. The main results were partially in favor of blended learning viability; it was found that not only students performed better in their exams during the pandemic era, but also their attitudes towards blended learning were mostly positive. It was indeed clear that blended learning had a positive impact on students’ performance despite it being temporarily implemented as an alternative to face-to-face learning